The evolving urban planning The Case of The City of Yogyakarta - Hadi Sabari Yunus (Indonesian Journal of Geography, 1991)
This article is to present the changing urban plans of the city of Yogyakarta and their impacts on its physical appearance. An intensive study of extensive materials is carried out in the library and governmental institutions particularly, the regional planning board of the city of Yogyakarta. By comparing the earlier simplest plan, to the recent one, a pronounced development of the respective plan can be detected. There were five types of Yogyakarta's plan i.e. Mangkubumi's Plan, Thomas Karsten's Plan, Putuhena's Plan, Purbodiningrat's Plan and the present plan which will be reviewed here. Some conclusions are particularly directed toward the present plan because this one is not more than a synthesis of the previous plans and the inputs are expected in order to be used for further elaboration